Knowledge overconfidence among entrepreneurs from Austria and North Macedonia - Ilieva, Viktorija; Janeska iliev, Aleksandra; Debarliev, Stojan; Nakov, Leonid; Drakulevski, LJubomir; Brudermann, Thomas (Nomos Verlag, 2022)
Entrepreneurial decision-making is often characterized by unrealistic optimism. This so-called “overconfidence bias” has consequently received an increasing amount attention from the authors of literature on entrepreneurship research. Most empirical studies, however, that target the overconfidence bias have been conducted with students or samples from the general population. This study contributes to the entrepreneurial decision-making literature by explicitly targeting entrepreneurs from Austria and North Macedonia (n = 187), defined as individuals who have started their own businesses or are in the process of doing so. The entrepreneurs were asked to complete a general-knowledge questionnaire and to estimate the accuracy of their answers. The results suggest that the most of these entrepreneurs exhibit overconfidence (and some, underconfidence) with regard to the accuracy of their knowledge. Significant differences were observed between the bias scores and confidence scores of the Austrian and Macedonian respondents, but not the accuracy scores. The so-called “hard-easy effect,” which indicates that individuals display overconfidence when answering hard questions, but underconfidence when answering easy questions, was observed among the Austrian but not among the Macedonian entrepreneurs.